Реалізація інформаційної культури вчителя як необхідної умови конкурентоспроможності в умовах євроінтеграції - Шовш Катерина; Soós Katalin; Shovsh Katerina (Вид-во МДУ, 2017)
Abstract. In the present article, peculiarities o formation of the information culture of future pedagogues and teachers are analyzed; the role of telecommunication technologies in the process of teaching students, their influience on cognitive interests and ont he informatization of education is examined; peculiarities of use of educational activities are studied. The purpose of the article is to show and reveal the importance of development and implementation of the information culture of the future pedagogues and students by means of telekommunication technologies, whose cognitive activity is the basis for the development of independence, disclosure of abilities and inclitions, creative educational and cognitive activities that act as means to satisfy the student’s spiritual needs, his\her interests, self-expression and self-realization. The nethod ofanalysis of accumulated knowledge and information on scientific literature and experience was used in the work. The search for ways and means of forming the cognitive activyti of pupils and students is connected, ont he one hand, with social processes in modern society;ont he other hand,with new technical opportunities for obtaining knowledge. The rapid development of yhe technical and software capabilities of personal computers , the dissemination of information and communication, as well as creative technologies estabilish real opportunities for their use in the edication system to develop the creative potential of the person in the education process and ensure the contiunity of studies between various levels of educational institutions. Telecommunication technologies, as one of the modern technical means, reqire careful analysis of the possibility of its application in the educational process. In order to implement new forms and methods of teaching the use of telecomunication technologies, it is useful to know their modern types and capabilities, as well as pedagogical technologies that are already implemented on their basis. Results of the studay. In conclusion , when organizing the educational process, it should be borne in mind that new generetions of children who come to school , live in an informative, dynamic, emotionally tense environment and it is a challenge for teachers.Information technology is becoming a powerfull multifunctional traning tool. Thus, pupils get used to live in the information environment; it promotes the involvement of schoolchildren in information culture.

Резюме. У статті аналізуються особливості формування інформаційної культури майбутніх педагогів, учителів, розглянуто роль телекомунікаційних технологій в процесі навчання студентів, їх вплив на пізнавальний інтереc та на інформатизацію освіти; особливості застосування освітніх можливостей телекомунікаційних технологій, розвиток і напрями подальшого їх використання у навчальній діяльності. Метою статті є показати та розкрити важливість розвитку та реалізації інформаційної культури майбутнього педагога, студента засобами телекомунікаційних технологій, пізнавальна активність яких є основою розвитку самостійності, розкриття здібностей та нахилів, творчої навчально-пізнавальної діяльності,виступаючи засобом задоволення духовних потреб студента, його інтересів, самовираження та самореалізації.
Implementing Teacher Information Culture as a Prerequisite for Competitiveness in the Conditions of European Integration
http://nbuv.gov.ua/UJRN/nvmdupp_2017_2_70
Keywords: освіта; студент; інформаційна культура; педагогічні технології; телекомунікаційні технології